2011
DOI: 10.1371/journal.pone.0024916
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Spin-Dried Mammalian Cells

Abstract: This study reports an alternative approach to achieve vitrification where cells are pre-desiccated prior to cooling to cryogenic temperatures for storage. Chinese Hamster Ovary (CHO) cells suspended in a trehalose solution were rapidly and uniformly desiccated to a low moisture content (<0.12 g of water per g of dry weight) using a spin-drying technique. Trehalose was also introduced into the cells using a high-capacity trehalose transporter (TRET1). Fourier Transform Infrared Spectroscopy (FTIR) was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…The HepG2 cells provisioned with intracellular trehalose and LEA proteins are not stable at room temperature in the dried state and begin losing viability if not rehydrated within minutes; the loss of viability can be greatly retarded by immediate storage of the dried cells at liquid nitrogen temperatures (34). Our FTIR measurements for the spin-dried samples indicate a T g of approximately 4.5°C, which means that the cells do not exist in a vitrified state at room temperature.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The HepG2 cells provisioned with intracellular trehalose and LEA proteins are not stable at room temperature in the dried state and begin losing viability if not rehydrated within minutes; the loss of viability can be greatly retarded by immediate storage of the dried cells at liquid nitrogen temperatures (34). Our FTIR measurements for the spin-dried samples indicate a T g of approximately 4.5°C, which means that the cells do not exist in a vitrified state at room temperature.…”
Section: Discussionmentioning
confidence: 78%
“…To our knowledge, both the short-term membrane integrities and the long-term viabilities obtained after immediate rehydration in this study are the highest yet reported for mammalian cells dried uniformly to a water content below 0.12 g H 2 O/g dry weight. As we have discussed previously in more detail (34), traditional drying procedures result in substantial spatial nonuniformity, such that regions with higher residual water are prone to higher rates of chemical reactions that can foster unwanted metabolic processes, energy depletion, and cell degradation. Reduced molecular motion, such as that observed in glassy states, is an important requirement for storage of desiccated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the successful desiccation and long-term storage of mammalian cells at ambient temperature is yet to be achieved, with the most notable exception being the dried storage of anucleated platelets (1,(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%